2014
DOI: 10.1371/journal.pone.0088607
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Localization of Rabbit Hepatitis E Virus and Antigen in Systemic Tissues from Experimentally Intraperitoneally Infected Rabbits

Abstract: Rabbit hepatitis E virus (HEV) is a novel genotype of HEV, and is considered to pose a risk of zoonotic transmission. Research into the systemic distribution of rabbit HEV in rabbits during different periods of infection has rarely been reported. To better understand this virus, we infected rabbits with second-passage rabbit HEV via an intraperitoneal route. After inoculation, the infection showed two types, temporary and constant infection. The detection of HEV RNA in the feces varied with time, and serum ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
(45 reference statements)
6
19
0
1
Order By: Relevance
“…Although no clinical signs were observed, the liver-to-body weight ratios of inoculated gerbils were greater than those of control group. The liver enzyme levels in the experimental group were significantly higher than in the negative control group, which is consistent with previous reports (Kabrane-Lazizi et al, 1999;Huang et al, 2009;Li et al, 2009;Kasorndorkbua et al, 2003;Mao et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although no clinical signs were observed, the liver-to-body weight ratios of inoculated gerbils were greater than those of control group. The liver enzyme levels in the experimental group were significantly higher than in the negative control group, which is consistent with previous reports (Kabrane-Lazizi et al, 1999;Huang et al, 2009;Li et al, 2009;Kasorndorkbua et al, 2003;Mao et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Immunohistochemistry and Western-blotting results have shown that HEV antigen is expressed in the liver and demonstrated that one of the target tissues of HEV is the liver (Mao et al, 2014). The finding that HEV RNA replication in the liver is consistent with HEV ORF3 antigen expression by Western-blotting is evidence of HEV replication and HEV antigen expression in the livers of Mongolian gerbils (Williams et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Several other animal models including pigs, rabbits, rodents and chickens that are naturally infected with particular HEV genotypes have recently been established for the study of various aspects of HEV infection [19]. For example, pigs and rabbits were used to demonstrate the existence of extrahepatic sites of replication by immunohistochemistry and detection of negative strand of HEV RNA [21,22]. The presence of residual infectious virus particles in food products after heat treatments was assessed using an in vivo experimental model in pigs [23].…”
Section: Basic Virologymentioning
confidence: 99%
“…In various publications, the applicability of antigen detection systems for the detection of viraemic patients and blood donors as well as for the follow-up of infections of experimental animals were investigated [164,165,166,167,168]. A relatively good correlation between the results of antigen detection systems and the NAT results were observed in hepatitis cases in India [164,167].…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%